Desorption of Hydrophobic Organic Chemicals from Fragment-Type Microplastics - Lee, Hwang; Byun, Da Eun; Kim, Ju Min; Kwon, Jung Hwan (Ocean Science Journal, 2018)
Microplastics provide an important medium for hydrophobic organic chemicals (HOCs), and the desorption of HOCs from microplastics is an important process for the dynamics of HOCs associated with microplastics. Although desorption kinetics has been studied for microplastics with ideal geometries, most of the microplastics isolated from the environment are irregular fragment-type microplastics. This study investigated the desorption of six model HOCs from polyethylene (PE) and polypropylene (PP) fragments to artificial seawater and compared the results with those predicted assuming ideal geometries (e.g., sphere and infinitely flat sheet) of microplastics. The experimental desorption was explained well by the model predictions with the characteristic radius for a sphere and the thickness for a plate estimated from visual imaging. The mass fraction remaining at the later stage of desorption was higher than the model simulation assuming a single characteristic length, likely due to the heterogeneity of the particle size distribution. Although there are inevitable uncertainties, it would be useful to assign a single length dimension in desorption modeling for even fragment-type microplastics, especially for the estimation of desorption half-life.
Keywords: Biot number; desorption kinetics; diffusion coefficient; partition coefficient; plastic debris